Prevalence and Determinants of Smoking and Smokeless Tobacco in the Rural Population of Karnataka, India - Dinesh Rajaram; Shalini Chandrashekar Nooyi; Pruthvish Sreekantaiah; Shalini Pradeep; Anjana George (Masters Program in Public Health, 2023)
Background: Tobacco is known as a major cause of various preventable non-communicable diseases and kills half of all its users. With a greater prevalence in the rural community compared to the urban, this global health burden is substantially malignant. This study aimed to bridge the gap in the lack of adequate statistical information pertaining to prevalence and determinants of smoking and smokeless tobacco use in the rural population of Karnataka.Subjects and Method: This randomized community interventional study was conducted in primary health center areas of Karnataka, India. A total of 4,576 persons were interviewed (2,087 males and 2,489 females). Subjects ?30 years of age and residents for a minimum of six months were included. Mentally challenged, bedridden or differently abled subjects were excluded. The study employed a validated questionnaire adapted from the WHO STEPS questionnaire concerning demographical information, behavioral, physical, and biochemical measurements. Besides tobacco, informa-tion on use of beedis, cigarettes, and smokeless tobacco products (snuff, chewing tobacco) were also elicited. Data analysis of socio-demographic characteristics (age, educational/ marital/ occupational status) was carried out only for the participants with a current smoking habit. Data were analyzed using SPSS Version 18.0.Results: The overall prevalence rate of current smoking and smokeless tobacco habit in the study population was 54.8% (95%CI= 53.40 to 56.20) and the prevalence rate of ever/past users was 39.7% (95%CI= 38.26 to 41.10). Genderwise analysis predicted a higher prevalence of males currently smoking, and among them, most were 50 to 59 years of age (43.3%), illiterate (42.7%), widowed/ separated (39.8%), unskilled (44%), and semi-skilled workers (30%).Conclusion: Both genders participate in tobacco use, prevalence of smoking was higher among men and consumption of smokeless tobacco was higher among women. Subjects aged 50-59 years, illiterate, divorced/widowed/separated and, involved in unskilled or semi-skilled labor exhibited greater prevalence of tobacco habit compared to other determinants.Keywords: noncommunicable diseases, global health, tobacco use, tobacco smoking, smokeless tobacco. Correspondence: Dinesh Rajaram, Associate Professor. Department of Community Medicine, M.S. Ramaiah Medical college and Hospital, Bengaluru 560054, Karnataka, India. Email id.: dinesh.gayathri6@gmail.com. Mobile: +919980336893.